THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH RELIGIOSITY AS A MODERATING VARIABLE - Rusni, Andi; Nur Fietroh, Muhammad (Journal of Business Studies and Management Review, 2024)
This study aims to examine the effect of remuneration and work discipline on employee performance, with religiosity as a moderating element. This study uses quantitative techniques and a causal approach in data analysis. The research population consists of all Regional Apparatus Organization (OPD) workers in West Sumbawa Regency (KSB), with a total of 3,133 individuals. The total sampling technique was used in this study. The sample size was determined using the Slovin formula, resulting in a total of 100 respondents. Data were analyzed using the Partial Least Squares (PLS) approach, which is part of the Structural Equation Modeling (SEM) analysis. The results showed that compensation and discipline positively and significantly affect employee performance. Religiosity effectively moderates the effect of compensation and work discipline on employee performance in OPD KSB. Increased remuneration and effective discipline enforcement can increase staff productivity and efficiency. Employee religiosity acts as a moderator that strengthens the relationship between compensation, discipline, and performance. Employees with high levels of religiosity will feel a greater effect of both elements on their performance, suggesting that spiritual values and work ethics are interrelated and can encourage a more productive work environment.